PENGARUH BACK MASSAGE DENGAN AROMATERAPI ESSENTIAL OIL LAVENDER TERHADAP PENURUNAN INTENSITAS NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI KLINIK BDN. HELMI TARIGAN TAHUN 2023 - Nelli, Ermeida (Politeknik Tiara Bunda, 2023)
Back pain is one of the discomforts often felt by pregnant women entering the third trimester. Handling to reduce back pain in pregnant women, can use complementary care, one of which is by providing back massage. Back massage action can be done using lavender essential oil aromatherapy. The purpose of this study was to determine the effect of back massage with lavender essential oil aromatherapy on the back pain scale in pregnant women before and after the intervention. The research method used a quasy experimental one group pretest-posttest design. The population of this study were pregnant women at the Rizka Permata Midwife Clinic in Depok as many as 30 pregnant women, with a total research sample of 15 third trimester pregnant women with complaints of back pain, with the sampling technique using purposive sampling. The results of the study after comparing the back pain scale before and after being given the intervention obtained an average prestest of 0.00 and posttest of 6.50, this shows a difference in pain scale with the results of p-Value = 0.001 <0.05, which means that there is an effect of back massage with lavender essential oil aromatherapy on reducing back pain in third trimester pregnant women at the Bdn. Helmi Tarigan Clinic. It is expected that pregnant women who experience back pain can know how to handle it using back massage therapy with lavender essential oil aromatherapy.